Gender Role, Gender Identity and Sexual Orientation in CAIS ("XY-Women") Compared With Subfertile and Infertile 46, XX Women. Issue 1 (2nd January 2016) - Brunner, Franziska; Fliegner, Maike; Krupp, Kerstin; Rall, Katharina; Brucker, Sara; Richter-Appelt, Hertha
Abstract : The perception of gender development of individuals with complete androgen insensitivity syndrome (CAIS) as unambiguously female has recently been challenged in both qualitative data and case reports of male gender identity. The aim of the mixed-method study presented was to examine the self-perception of CAIS individuals regarding different aspects of gender and to identify commonalities and differences in comparison with subfertile and infertile XX-chromosomal women with diagnoses of Mayer-Rokitansky-Küster-Hauser syndrome (MRKHS) and polycystic ovary syndrome (PCOS). The study sample comprised 11 participants with CAIS, 49 with MRKHS, and 55 with PCOS. Gender identity was assessed by means of a multidimensional instrument, which showed significant differences between the CAIS group and the XX-chromosomal women. Other-than-female gender roles and neither-female-nor-male sexes/genders were reported only by individuals with CAIS. The percentage with a not exclusively androphile sexual orientation was unexceptionally high in the CAIS group compared to the prevalence in "normative" women and the clinical groups. The findings support the assumption made by Meyer-Bahlburg (2010 ) that gender outcome in people with CAIS is more variable than generally stated. Parents and professionals should thus be open to courses of gender development other than typically female in individuals with CAIS.